Labour Demand with Heterogeneous Labour Inputs after the Transition in Hungary, 1992-1999 - and the Potential Consequences of the Increase of Minimum Wage in 2001 and 2002 - Gabor Kertesi; Janos Kollo (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2002)
The paper analyses changes in the demand for unskilled, young skilled, and older skilled workers during the post-communist transition in Hungary. Systems of cost share equations derived from the translog cost function are estimated for cross-sections of large firms observed in the period 1992-99. Following the 'transformational recession' the own-price elasticities of labour and capital were stabilized at levels observed in several developed market economies. Unskilled and skilled labour are estimated to be p-complements, and younger and older skilled workers p-substitutes. Capital and labour appear to be p-substitutes with unskilled labour having the highest elasticity of substitution. Further results hint at the existence of nonnegligible scale effects and the non-neutrality of technical change. The estimated wage elasticities give us the opportunity to evaluate consequences of some governmental policies. As minimum wage was doubled in nominal terms between 1999 and 2002 in Hungary it was evident to apply these results to this highly relevant issue. In the second part of the paper we try to evaluate the potential demand consequences of this. Based on the earnings distributions of the Wage Survey of 1999 (a large individual level data set) we make several predictions concerning these consequences.
Keywords: 330